Prenos premoženja na zakonca z namenom izigranja upnikov - Dugar, Gregor (Podjetje in delo, 2014)
The debtor who does not wish to settle his debt often transfers his property to a third person in order to conceive it from the creditor. This third person is usually his or her spouse, because in such a case the transferred property can still be used by the debtor. The author discusses the validity of such legal transactions between spouses and analyses different legal bases, by which the creditor can get his debt paid.
Keywords: dolgovi; dolžniki; premoženje; prenos; upniki; zakonci